Euroregion Beskidy jako stymulator rozwoju - analiza na przykładzie turystyki - Greta, Marianna (Wydawnictwo Politechniki Łódzkiej, 2015)
The study includes three parts, i.e. one generał and two detailed. In the generał part a tourism was described as the branch of economy, kinds and functions of the tourism according to the euroregional aspect. The detailed part is regarding to the Beskidy Euroregion and its' developmental specificity and activities of the EU structural assistance in the form of selected proj ects of the touristic relevancy and character. Creating at the joint border of three countries (Poland - the Czech Republic - Slovakia) structure of the peripheral area euroregion which has chances to include, through the tourism, into the realization challenges of smart specialisation.

Opracowanie obejmuje trzy części, tj. ogólną i dwie szczegółowe. W części ogólnej przedstawiono turystykę jako gałąź gospodarki, jej rodzaje i funkcje, odnosząc je jednocześnie do aspektu euroregionalnego. Część szczegółowa dotyczy Euroregionu Beskidy i jego specyfiki rozwojowej oraz aktywności unijnej pomocy strukturalnej w formie wybranych projektów o znaczeniu i charakterze turystycznym Powołanie u styku granic trzech krajów (Polska - Czechy - Słowacja) struktury euroregionu zaaktywizowało potencjał endogeniczny tego peryferyjnego obszaru, który ma szanse poprzez turystykę włączyć się w realizację wyzwań smart specialisation
The Beskidy euroregion as the stimulus of the development - analysis on the example of the tourism